Demand and price analysis : some examples from agriculture - Waugh, Frederick Vail. (Washington, D.C. : Economic and Statistical Analysis Division, U. S. Dept. of Agricultutre, 1964)
This expresses accurate forecast of consumption and prices for making intelligent adjustments in production and marketing
Includes bibliographical footnotes and index.
mf 21/01/2019
Loans
Keywords: Supply and demand; Prices